SAT0152 Real-life infliximab and adalimumab trough level and anti-drug antibody measurements in rheumatology: the finnish experience. (15th June 2017) - Ho, D; Valtanen, S; Havana, M; Kröger, L; Eklund, K; Jokiranta, S
Abstract : Background: Therapeutic drug monitoring of TNF inhibitors (TNFi) may optimize clinical benefits while at the same time reducing financial costs and risk of adverse events 1, 2 . Monitoring the TNFi trough levels (TLs) and the anti-drug antibodies (ADAbs) can provide relevant information to make rational adjustments to therapy if indicated. Objectives: To identify distributions and trends in infliximab (IFX) and adalimumab (ADL) TLs and ADAbs from clinically requested, real-life samples from Finnish patients with rheumatoid arthritis (RA), spondyloarthropathies (SpA), or juvenile idiopathic arthritis (JIA). Methods: Samples for TL and ADAbs were taken on a clinical basis in daily practice from four university hospitals and 15 central hospitals in Finland and sent for analysis to United Medix Laboratories. Samples were collected and analyzed from January 2012 to February 2016. TL measurements were performed by enzyme-linked immunosorbent assay (either at Sanquin laboratories, Amsterdam, The Netherlands, or in Helsinki, Finland using Promonitor ELISA, Progenika Biopharma). TLs from 2–10 μg/ml (IFX) or 5–10 μg/ml (ADL) were considered as general target ranges. ADAb measurements were performed by radioimmunoassay (Sanquin). 1762 TL (1241 patients), 1598 ADAb (1203 patients), and 860 combined TL and ADAb samples (718 patients) were analyzed. Statistical analyses were performed by SPSS (IBM, Armonk, NY). p<0.05 was considered statistically significant. Results: The highest proportions of samples with very low TLs (<0.1 μg/ml) were seen in IFX-treated RA patients (14.5%) and ADL-treated SpA patients (12.6%). The proportion of all samples in the general target range was 51.3% (IFX) and 33.4% (ADL). A greater proportion of ADL RA and SpA samples had possibly supratherapeutic (>10 μg/ml) TLs (RA: ADL, 22.9% vs IFX, 10.4%, p<0.01 and SpA: ADL, 21.4% vs IFX, 15.0%, p=0.05). A greater proportion of ADL JIA samples had TLs >10 μg/ml (ADL, 54.5% vs IFX, 36.3%, p<0.01). Proportions of samples with ADAbs (>12 AU/ml) ranged from 18.0% (IFX RA) to 28.6% (ADL SpA). A greater proportion of ADL samples with TLs of 2–5 μg/ml and detectable ADAbs (>12 AU/ml) (RA: ADL, 3.3% vs IFX, 0%; SpA: ADL, 5.6% vs IFX, 0%; JIA: ADL, 3.4% vs IFX, 0.9%) was observed. Conclusions: IFX RA and ADL SpA samples had the highest proportions of very low TLs. Compared to IFX, greater proportions of ADL samples (all indications, particularly JIA) had TLs >10μg/ml. Proportions of samples with ADAbs >12 AU/ml ranged from 18.0% to 28.6%. Compared to IFX, a greater proportion of ADL samples with possibly therapeutic TLs had detectable ADAbs. References: Bendtzen K. Anti-TNF-alpha biotherapies: perspectives for evidence-based personalized medicine. Immunotherapy 2012;4:1167–1179. Laine J, Jokiranta TS, Eklund KK, Väkeväinen M, Puolakka K. Cost-effectiveness of routine measuring of serum drug concentrations and anti-drug antibodies in treatment of rheumatoid arthritis patients with TNF-α blockers. Biologics 2016;10:67–73. Disclosure of Interest: None declared